Doença de Alzheimer na família: repercurssões sobre o seu funcionamento - Neumann, Solange Maria Freire (2010)
Alzheimer's disease accounts for more than half of dementia and has no known your cure. So when it raises this diagnosis, patients and families faced with the implications of this disease, which presents a course of progressive decline and global cognitive function. This study aimed to study the general social and psychological impact that occur in families of patients with Alzheimer's disease. Specifically, we sought to identify the feelings experienced and the needs felt by the family. This is a qualitative research and the research sample was comprised of six family members of patients with Alzheimer's disease who were treated at the Cognitive Neurology and Behavior (ANCC), General Hospital Sands in Recife. The instrument was a structured interview containing questions related to the goals and socio-demographic data of the family. The technique used for data analysis was the Thematic Content Analysis. The results showed that the act of caring for a relative with Alzheimer's disease leads to feelings of anxiety, confusion, helplessness and sadness, which are intensified with the worsening of the condition. The main impact occurred in the family refers to a change in his routine and the relationship established between the patient and other family members. When care is taken by one person, the physical and mental health interferes in social life and, consequently, the quality of life of the caregiver. In this study, we realize how important to broaden the discussion and knowledge about Alzheimer's disease, focused on the family and especially the caregiver. It is hoped that it can provide useful answers to the professionals who deal with the subject, to develop interventions more targeted and effective, as well as families seeking guidance and help to minimize their distress